Inorganic phosphorus fractions and phosphorus availability in long term fertilizer cum manurial trials under coconut cultivation - Neenu, S.; Bhat, Ravi; Selvamani, V.; Subramanian, P. (Journal of Plantation Crops, 2023)
Phosphorus is one of the major nutrients required for coconut production. The information about the fate of native and applied phosphorus in soil is essential for better management of the nutrient. The changes on inorganic P fractions and P availability in soil after 43 years of coconut cultivation were studied from a long term fertilizer cum manurial experiment at CPCRI, Kasaragod. There were 6 treatments viz. tillage with organic and inorganic fertilizer, tillage with inorganic fertilizer, inorganic fertilizers with basin forking, tillage alone, herbicide application without tillage and fertilizer and the control. Soil samples were taken at two depths (0-30 and 30-60 cm) from coconut basin for analysis. Phosphorus was fractionated into Easily Soluble P (ES-P), Aluminium P (AI-P), Iron P (Fe-P), Calcium P (Ca-P) and Reductant Soluble P (RS-P) through sequential extraction. The dominant phosphorus fraction in the coconut basin at 0-30 cm depth was Ca-P and the trend is as follows: Ca-P> Fe-P> RS-P>Al-P>ES-P. However, at 30-60 cm depth, Fe-P became the dominant fraction and the trend is Fe-P>Ca-P>RS-P>Al-P>ES-P. Long-term phosphorus fertilization would facilitate the accumulation of soil Ca-P, and thus improve soil P availability. In the interspaces, Fe-P was the dominating fraction in both the depths followed by Ca-P and RS-P. The diﬀerence in P fractions in fertilized and non-fertilized plots clearly showed that the fertilized plots have high content of all the inorganic phosphorus fractions in both the depths. Application of mineral P along with forking in basin showed a high concentration of all the inorganic P fractions compared to other fertilizer applied treatments.